Hubungan antara kecerdasan emosi dengan perilaku agresif remaja dan implikasinya dalam bimbingan dan konseling - Ulya Illahi; Neviyarni Neviyarni; Azrul Said; Zadrian Ardi (JRTI (Jurnal Riset Tindakan Indonesia), 2018)
This research is motivated by the number of adolescents who behave aggressively, such as hitting, kicking, yelling, cursing, slandering. Aggressive behavior is an action that aims to hurt other people both physically and verbally. One of the factors that is thought to influence is emotional intelligence. This study aims to: (1) describe emotional intelligence, (2) describe the aggressive behavior of adolescents, and (3) test the significance of the relationship between emotional intelligence and adolescent aggressive behavior. This study uses quantitative methods with descriptive correlational types. The population of this study was 300 students of MAN 1 Tanah Datar who were enrolled in the July-December semester of the 2018/2019 academic year and a sample of 178 students selected by Stratified Random Sampling. The instrument used in this study was ascale model Likert. Data were analyzed by descriptive statistical techniques andtechniques Pearson Product Moment with the help of the SPSS for Windows 20 program. Research findings show that: (1) adolescent emotional intelligence is in the high category, (2) adolescent aggressive behavior is in the moderate category, (3) and there is a significant negative relationship between emotional intelligence and aggressive behavior of adolescents with a correlation coefficient of -0.431 and level significance of 0,000. One of the factors that influence adolescent's aggressive behavior is emotional intelligence. This research is important so that aggressive behavior of adolescents can be minimized by emotional intelligence, because adolescents who manage theirintelligence are emotionalwell able to control themselves so they do not take aggressive actions.